Comparison Between Soil Improvement Design Method of Replacement and PVD Installation for Soft Soil Embankment, Case Study: Probolinggo – Banyuwangi Toll Road Project Section 3 Sta 23+075 – 23+670 - Wardani, Esti Kusuma; Kazhimi, Reza (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
The Probolinggo – Banyuwangi Toll Road, part of Trans Java Toll Road, is one of the strategic projects which connects the west to the east of the island of Java. On this toll road, precisely in section 3 STA 23+075 – 23+670, the toll road structure and pavement construction stands on soft ground with varying depths, with the deepest point being around 9 meters. It is concerned that the presence of soft soil which is quite deep will cause damage to the pavement, which will cause discomfort for road users if the soft soil cannot be improved properly. In this study, several alternatives are designed which will later be used as considerations for the project owner to determine the most effective method for improving soft soil at that location. The method used is subgrade replacement which will later be compared with the use of PVD along with estimated costs for each method. Apart from that, an analysis was also carried out regarding compliance with the rate of residual settlement regulations from the Director General of Highways, namely less than 2 cm per year and less than 10 cm per 10 years. From the study results, it was found that the rate of settlement of all variations of soft soil and replacement had met the Bina Marga regulations. In addition, a comparison of PVD cost requirements with replacement showed that PVD requires lower costs than replacement with a maximum time of ±5 weeks so that it can be concluded as the best alternative method.